A semi-analytical fracture high-conductivity location diagnostic method for vertically fractured wells in multilayered reservoirs: field case study - Zhang, Yijun; Wang, Wanbin; Ma, Dudu; Xia, Yun; Wang, Ningbo; Cheng, Shiqing; Wei, Cao (Frontiers in Energy Research, 2024)
Deep multilayered reservoirs are usually developed using multilayered fracturing techniques; however, the non-uniform placement of proppant causes uneven distribution of fracture conductivity.This study introduces a semi-analytical well test model for hydraulically fractured wells in multilayered reservoirs, accounting for varying fracture conductivity within the hydraulic fracture. The model is built upon the point source function, boundary element method, Duhamel theorem, and pressure superposition principle. Verification tests are conducted to ensure calculation accuracy.Sensitivity analysis is performed on key parameters, encompassing the transmissibility factor, storativity factor, fracture extension, and fracture conductivity. The findings indicate that (i) Increased heterogeneity among layers correlates with a more pronounced pressure drop; (ii) Poorly-propped fracture conductivity influences the duration of bilinear flow, becoming negligible after linear flow;(iii) The model's applicability extends to other multilayered reservoirs (e.g., carbonate reservoirs) with minor adjustments. Lastly, a case study from Xinjiang oilfield is presented to demonstrate that the proposed method can derive reservoir and fracture properties for each layer individually. This study contributes to a deeper understanding of the potential of pressure data in characterizing multilayered reservoirs.